(untitled) (Journal of Geography and Environmental Management, 2025)
Amidst dynamic socio-economic transformations and significant regional disparities, the Republic of Kazakhstan faces the imperative for a deeper and spatially-oriented understanding of its socio-demographic processes. The purpose of this scientific research is to explore the potential and practical application of geoinformation systems (GIS) for mapping, analyzing, and visualizing key socio-demographic indicators in Kazakhstan. The core idea of this work is to demonstrate how spatial analysis can reveal hidden patterns and aid in the development of more targeted and effective sustainable development strategies. The scientific significance of the study is defined by its contribution to the methodology of interdisciplinary analysis, integrating geographic, demographic, and statistical approaches, while its practical significance lies in the development of tools for informed governmental and regional management. The research methodology involves the collection and systematization of statistical data (population censuses, administrative data), their geocoding, the creation of a unified geoinformation database, and the application of spatial analysis methods such as thematic mapping, cluster analysis, buffer analysis, and accessibility analysis. The main results indicate that GIS mapping clearly identifies regional disparities in population density, urbanization, migration flows, age-sex structure, and access to social services. The analysis demonstrates how spatially linking data makes it more meaningful for decision-making. The value of the conducted research lies in developing a comprehensive approach to the spatial analysis of demographic data, which has been applied fragmentarily in Kazakhstan until now, and in creating a foundation for more effective social infrastructure planning. The practical significance of the work’s outcomes lies in their potential use for optimizing resource allocation, targeted funding of regional programs, and enhancing the efficiency of public policy implementation in demography and social development